Development of craft drinks with oat milk and fruit and berry powders - Dudarev, Igor (Lutsk : LNTU, 2024)
Consumption of plant-based milk is growing every year, especially among allergy sufferers and lactose intolerant people. The development of beverages based on it with the addition of nutrients and improved taste properties is a trend among soft drink manufacturers. The purpose of the article is to develop recipes for craft drinks with oat milk and powders from freeze-dried fruits and berries, as well as to determine their sensory and physicochemical characteristics. The research was conducted using the method of expert evaluation of the sensory characteristics of drink compositions, the calculation method for calculating the nutritional and energy value of drinks, qualimetry methods for calculating a comprehensive indicator of drink quality, methods for determining the physicochemical characteristics of drinks, the Color Detector & Catcher mobile application for determining the colour of drinks using the RGB additive colour model, and methods of statistical data processing using Mathcad 14 software. For drinks based on plant-based milk, it is proposed to use powders from freeze-dried fruits and berries as a recipe components. Freeze-dried plant powders preserve the colour, smell and taste of natural raw materials, as well as their nutrients. Model compositions of drinks with oat milk and powders made from freeze-dried mango, blueberries, strawberries, bilberries and raspberries were developed. The best drink compositions with high sensory properties (taste and smell, colour, appearance and consistency) were identified by an expert evaluation method. The density and active acidity of the developed drink compositions were investigated and their nutritional and energy values were calculated. It was found that the density of drinks increases with the increase in the content of fruit and berry powders, and the pH of drinks decreases. It has also been found that an increase in the content of freeze-dried fruit and berry powders in a drink leads to an increase in the content of protein and carbohydrates. Fruit and berry powders fortify drinks with nutrients and diversify their taste and aroma. The proposed drinks can be recommended for implementation in food industry enterprises, craft food production facilities and restaurants.
Keywords: plant-based milk; drink recipe; drink properties; freeze-dried fruit; freeze-dried berries